Relationship between inhaled steroids and anthropometric status of pediatric patients with chronic asthma - Harjoedi Adji Tjahjono; Ery Olivianto; Alfidha Muntaz; Irfan Agus Salim; Fadilah mutaqin (Medical Faculty of Brawijaya University, Indonesia, 2023)
Background: Asthma is a chronic inflammatory respiratory disease characterized by breathlessness, wheezing, and coughing symptoms. Asthma management aims to control the frequency of asthma exacerbations and ensure optimal growth and development in children. Inhaled steroids are anti-inflammatory medications that inhibit the synthesis of pro-inflammatory cytokines such as IL-4, IL-9, IL-13, and IL-17, which play a role in the pathogenesis of asthma. However, using inhaled steroids at high doses and for a long duration can have side effects on children's height. This research aims to examine the relationship between the use of inhaled steroids and the growth in height of children with asthma. Methods: simple linear regression analysis and multiple linear regression analysis. Results: the analysis indicate a correlation between daily dose and height increment in children aged 5-10 years (p = 0.005 < 0.05), but no significant correlation was found in children aged 10-18 years (p = 0.722 > 0.05). The analysis of total duration shows a correlation with height increment in both age groups (5-10 years, p = 0.035 < 0.05; 10-18 years, p = 0.001 < 0.05). The analysis also reveals a correlation between the simultaneous total duration and total dose with height increment in both age groups (5-10 years, p = 0.005 < 0.05; 10-18 years, p = 0.008 < 0.05). Conclusion: this study found a correlation between daily dose and height in both age groups, a correlation between total duration and height in the 5-10-year-old age group, and a correlation between simultaneous total duration and total dose with height in both age groups.